Altered skeletal muscle metabolic pathways, age, systemic inflammation, and low cardiorespiratory fitness associate with improvements in disease activity following high-intensity interval training in persons with rheumatoid arthritis - Brian J. Andonian; Andrew Johannemann; Monica J. Hubal; David M. Pober; Alec Koss; William E. Kraus; David B. Bartlett; Kim M. Huffman (Arthritis Research & Therapy, 2021)
Abstract Background Exercise training, including high-intensity interval training (HIIT), improves rheumatoid arthritis (RA) inflammatory disease activity via unclear mechanisms. Because exercise requires skeletal muscle, skeletal muscle molecular pathways may contribute. The purpose of this study was to identify connections between skeletal muscle molecular pathways, RA disease activity, and RA disease activity improvements following HIIT. Methods RA disease activity assessments and vastus lateralis skeletal muscle biopsies were performed in two separate cohorts of persons with established, seropositive, and/or erosive RA. Body composition and objective physical activity assessments were also performed in both the cross-sectional cohort and the longitudinal group before and after 10 weeks of HIIT. Baseline clinical assessments and muscle RNA gene expression were correlated with RA disease activity score in 28 joints (DAS-28) and DAS-28 improvements following HIIT. Skeletal muscle gene expression changes with HIIT were evaluated using analysis of covariance and biological pathway analysis. Results RA inflammatory disease activity was associated with greater amounts of intramuscular adiposity and less vigorous aerobic exercise (both p < 0.05). HIIT-induced disease activity improvements were greatest in those with an older age, elevated erythrocyte sedimentation rate, low cardiorespiratory fitness, and a skeletal muscle molecular profile indicative of altered metabolic pathways (p < 0.05 for all). Specifically, disease activity improvements were linked to baseline expression of RA skeletal muscle genes with cellular functions to (1) increase amino acid catabolism and interconversion (GLDC, BCKDHB, AASS, PYCR, RPL15), (2) increase glycolytic lactate production (AGL, PDK2, LDHB, HIF1A), and (3) reduce oxidative metabolism via altered beta-oxidation (PXMP2, ACSS2), TCA cycle flux (OGDH, SUCLA2, MDH1B), and electron transport chain complex I function (NDUFV3). The muscle mitochondrial glycine cleavage system (GCS) was identified as critically involved in RA disease activity improvements given upregulation of multiple GCS genes at baseline, while GLDC was significantly downregulated following HIIT. Conclusion In the absence of physical activity, RA inflammatory disease activity is associated with transcriptional remodeling of skeletal muscle metabolism. Following exercise training, the greatest improvements in disease activity occur in older, more inflamed, and less fit persons with RA. These exercise training-induced immunomodulatory changes may occur via reprogramming muscle bioenergetic and amino acid/protein homeostatic pathways. Trial registration ClinicalTrials.gov , NCT02528344 . Registered on 19 August 2015.